Robust ternary system of corncob-derived carbon quantum dots/ ZnFe2O4/graphene oxide for wastewater treatment - Wajeeha Qayyum; Noor Tahir; Muhammad Zahid; Saima Noreen; Muhammad Yaseen; Abeer A. AlObaid; Qamar Abbas; Ghulam Mustafa (BMC Chemistry)
Abstract Water contamination emerging from urban and industrial waste disposal is posing an alarming threat to human and marine life. Hence, it is imperative to take a crucial approach to lowering the overall cost and time of wastewater treatment. The efficiency of heterogeneous photo Fenton green wastewater treatment processes relies mainly on the morphology and surface interface properties of photocatalysts for harnessing maximum sunlight energy. This research work reports for the first time the hydrothermal synthesis of ternary zinc ferrite coupled with carbon quantum dots derived primarily from corncob biomass and supported over graphene oxide. The physiochemical properties and microstructure of magnetic graphene oxide anchored over carbon quantum dots included Fourier Transform Infrared Spectroscopy, Scanning Electron Microscope/Energy Dispersive X-ray, X-ray photoelectron spectroscopy, X-ray diffraction and Ultraviolet–Visible Spectroscopy. The effect of several factors on the photocatalytic degradation of Rhodamine B (RhB) dye was studied and maximum degradation was attained at optimized conditions of pH = 4, catalyst concentration (20 mg/100 mL), oxidant dose (10 mM) and degradation time (60 min). Response surface methodology was used to determine the optimization of various interacting parameters. The current research focused on the utilization of waste corncob biomass as a potential candidate for the novel ternary nanocomposite for effective treatment dye wastewater and reuse of treated dye water over wheat seeds germination.